2016
DOI: 10.1093/infdis/jiw385
|View full text |Cite
|
Sign up to set email alerts
|

Metalloproteinases and Brain Arterial Remodeling Among Individuals With and Those Without HIV Infection

Abstract: Background. This study tests the hypothesis that increased elastolytic activity is associated differentially with dolichoectasia in individuals with and those without human immunodeficiency virus (HIV) infection.Methods. Large arteries from 84 autopsied brains from HIV-positive individuals and 78 autopsied brains from HIV-negative individuals were stained for metalloproteinase 2 (MMP-2), MMP-3, MMP-9, tissue inhibitor of metalloproteinases 1 (TIMP-1), TIMP-2, CD68, and caspase 3. Average pixel intensity was au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
(26 reference statements)
2
8
0
Order By: Relevance
“…From this result, we conclude that a sufficient CD3 ϩ T cell count may be necessary to generate inflammatory responses in HIV that may lead to luminal reduction and possibly blood flow reduction. Hypertrophic outward remodeling as a response to intimal lymphocytic inflammation may relate to increased elastolytic and medium apoptosis, a phenomenon that we have previously described in the same cohort in association with adventitial macrophages (11) and that others have documented in aortic or coronary aneurysmal dilatation (12)(13)(14). It is possible that immunosuppression interacts with intimal CD3 ϩ T cells in a way that potentiates dilatation rather than constriction, as among those with a CD4 count of Ͼ200; it is also possible that dilatory effects are predicated on other cell populations.…”
Section: Discussionsupporting
confidence: 66%
“…From this result, we conclude that a sufficient CD3 ϩ T cell count may be necessary to generate inflammatory responses in HIV that may lead to luminal reduction and possibly blood flow reduction. Hypertrophic outward remodeling as a response to intimal lymphocytic inflammation may relate to increased elastolytic and medium apoptosis, a phenomenon that we have previously described in the same cohort in association with adventitial macrophages (11) and that others have documented in aortic or coronary aneurysmal dilatation (12)(13)(14). It is possible that immunosuppression interacts with intimal CD3 ϩ T cells in a way that potentiates dilatation rather than constriction, as among those with a CD4 count of Ͼ200; it is also possible that dilatory effects are predicated on other cell populations.…”
Section: Discussionsupporting
confidence: 66%
“…Furthermore, tetracycline therapy may decrease the risk for hemorrhage in patients with brain vascular malformations such as arteriovenous malformation and intracranial aneurysm (26). Interestingly, a recent study that investigated MMPs and brain arterial remodeling confirmed that high MMP-9 expression, alone or combined with low TIMP-2 expression, was associated with dolichoectasia in HIV-negative individuals; high expression of MMP-9, accompanied by expression of caspase 3, was associated with dolichoectasia in HIV-positive individuals (10). MMP-2 levels were found to be associated with cervical/intracranial carotid artery dolichoarteriopathies (11).…”
Section: Discussionmentioning
confidence: 99%
“…[42] A thinner media layer might be a preclinical stage in HIV vasculopathy development. [43] A study in China found that cerebrovascular endothelial dysfunction associated with HIV seropositivity may be important in the pathogenesis of cerebrovascular dysfunction. [44] CD8 + encephalitis, an emerging clinical entity pathologically associated with marked perivascular infiltrates with polyclonal CD8 + lymphocytes, may be a newly recognized HIV vasculopathy though further studies are needed to fully delineate the pathophysiological processes underlying this condition.…”
Section: Hiv-associated Cerebrovascular Disordersmentioning
confidence: 99%